2015
DOI: 10.1007/s11368-015-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterisation of surface waters, topsoils and efflorescences in a historic metal-mining area in Spain

Abstract: Purpose Mining activities generate large amounts of wastes that may contain potentially toxic elements (PTE), which, if released into the environment, may cause air, water and soil pollution long after mining operations have ceased. This paper describes the environmental relevance of efflorescences, topsoils and surface waters from the abandoned mine of Sierra Minera of Cartagena-La Unión, SE Spain. The exposure of the population to arsenic and the associated risk were also assessed. Materials and methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
(30 reference statements)
3
15
1
Order By: Relevance
“…Finally, Cu was 4-fold higher than its NGR (30 mg kg -1 ). Similar concentrations of Zn, Pb and Cd were found in tailings ponds from the Cartagena-La Unión mining district [11,57,58].…”
Section: Soil Properties Metal Concentration and Ert Imagingsupporting
confidence: 67%
“…Finally, Cu was 4-fold higher than its NGR (30 mg kg -1 ). Similar concentrations of Zn, Pb and Cd were found in tailings ponds from the Cartagena-La Unión mining district [11,57,58].…”
Section: Soil Properties Metal Concentration and Ert Imagingsupporting
confidence: 67%
“…Ryegrass productivity is restricted on mine tailings due to limiting nutritional (N, P, K), chemical (acidity, salinity, metal toxicity), and physical (low OM content, compaction) factors (Ye et al, 2002; Verdugo et al, 2010; Pérez‐Sirvent et al, 2016). The present study showed that incorporation of selected pig residues into Cauquenes tailings resulted in significantly increased ryegrass productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Using cadastral data, a random selection of housings was employed to guarantee the representativeness of study areas regarding demographic and socioeconomic characteristics. We (Sivry et al 2010, Patinha et al 2014, Pérez-Sirvent et al 2016. Pollution is spread in the polluted municipalities but does not spill over to the control areas.…”
Section: An Original Data Setmentioning
confidence: 99%